Evolution of the Yellow/Major Royal Jelly Protein family and the emergence of social behaviorin honey bees - Drapeau, Mark David; Albert, Stefan; Kucharski, Robert; Prusko, Carsten; Maleszka, Ryszard (Genome Research, 2006)
The genomic architecture underlying the evolution of insect social behavior is largely a mystery. Eusociality, defined by overlapping generations, parental brood care, and reproductive division of labor, has most commonly evolved in the Hymenopteran insects, including the honey bee Apis mellifera. In this species, the Major Royal Jelly Protein (MRJP) family is required for all major aspects of eusocial behavior. Here, using data obtained from the A. mellifera genome sequencing project, we demonstrate that the MRJP family is encoded by nine genes arranged in an ∼60-kb tandem array. Furthermore, the MRJP protein family appears to have evolved from a single progenitor gene that encodes a member of the ancient Yellow protein family. Five genes encoding Yellow-family proteins flank the genomic region containing the genes encoding MRJPs. We describe the molecular evolution of these protein families. We then characterize developmental-stage-specific, sex-specific, and caste-specific expression patterns of the mrjp and yellow genes in the honey bee. We review empirical evidence concerning the functions of Yellow proteins in fruit flies and social ants, in order to shed light on the roles of both Yellow and MRJP proteins in A. mellifera. In total, the available evidence suggests that Yellows and MRJPs are multifunctional proteins with diverse, context-dependent physiological and developmental roles. However, many members of the Yellow/MRJP family act as facilitators of reproductive maturation. Finally, it appears that MRJP protein subfamily evolution from the Yellow protein family may have coincided with the evolution of honey bee eusociality.